Gender Gap in Financial Decisions and Investments: Examining Gender Differences in Financial Decision-Making (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Research has demonstrated that financial illiteracy is across the board among women, and that many women are new to even the most basic economic ideas expected to settle on saving and investment decisions. This gender hole in financial literacy may add to the differential degrees of retirement readiness between women and men. In any case, little is thought about the determinants of the gender hole in financial literacy. Gender differences in investing have been pulling in high unmistakable quality in the scholarly plan. Therefore, it was proved that women are more hazardously disinclined than men and consequently with regards to investing they put more minimalistic ally and less in sums than men. The economic participation and access to the financial market between men and women is about equivalent and women hold comparative extents of total wealth in stocks and bonds. We have led a qualitative study to explore differences in hazard avoidance and presumptuousness between genders with regards to financial decisions. The gender differences in financial investment decisions are amazingly crude. The present study aims at evaluating Literature survey on the gender differences in investment and financial decisions.